Pengaruh Minat Membaca terhadap Mata Pelajaran Pendidikan Agama Kristen - David Kuwissy (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Abstract: Teachers are one of the determining factors for the success of every educational effort. That is why teachers must create innovations in the curriculum and always improve the abilities of their human resources through continuous learning. Reading is one of the four language skills. Language skills consist of speaking skills, listening skills, writing skills and reading skills. This paper uses kuantiatif method with a literature and wawancaca approach in obtaining data. The purpose of this topic is to find out how the influence of reading through the study of Christianity. Because, based on the existing facts, at SD Negeri Wamena there are some students who are not interested in the subject of Christian Religious Education. Students are more interested in other subjects. This is because the interest in reading by the students in the school has been provided with a library which also has books related to Christian Religious Education. Based on the results of research, Christian Religious Education Teachers are required to be even better and pay special attention to students so that students have a higher interest in reading.Keyword: Interest in Reading, Christian Religious Education, LearnersAbstrak: Guru merupakan salah satu faktor penentu keberhasilan setiap upaya pendidikan. Itulah sebabnya guru harus menciptakan inovasi dalam kurikulum serta selalu meningkatkan kemampuan sumber daya manusianya melalui belajar yang terus-menerus. Membaca adalah salah satu dari empat keterampilan berbahasa. Keterampilan berbahasa terdiri dari keterampilan berbicara, keterampilan menyimak, keterampilan menulis dan keterampilan membaca. Tulisan ini menggunakan metode kuanitatif dengan pendekatan literatur dan wawancaca dalam memperoleh data. Tujuan dari topik ini diulas untuk mengetahui bagaimana pengaruh membaca melalui pembelajaran agama Kristen. Sebab, berdasarkan fakta yang ada, di SD Negeri Wamena ada beberapa siswa yang kurang tertarik dengan mata pelajaran Pendidikan Agama Kristen. Siswa lebih tertarik dengan mata pelajaran yang lain. Hal ini disebabkan karena minat membaca para siswa di sekolah tersebut sudah disediakan satu buah perpustakaan yang juga terdapat buku-buku yang berhubungan dengan Pendidikan Agama Kristen. Berdasarkan hasil penelitian Guru Pendidikan Agama Kristen dituntut agar lebih baik lagi dan lebih memberi perhatian khusus bagi para siswa agar siswa memiliki minat membaca lebih tinggi.Kata Kunci: Minat Membaca, Pendidikan Agama Kristen, Peserta Didik